Grading System and Surgical Strategy for Temporal Bone Diffuse‐Type Tenosynovial Giant Cell Tumor. (28th October 2021) - Lin, Feng; Zhang, Yibo; Zhao, Peng; Kong, Dedi; Feng, Yisi; Dai, Chunfu
Abstract : Objectives: To develop a novel grading system and appropriate surgical approaches for patients with diffuse type tensosynovial giant cell tumor (D‐TGCT) of the temporal bone. Study Design: Retrospective cohort study. Methods: We retrospectively reviewed 31 patients with temporal bone D‐TGCT between June 2012 and July 2021. All patients underwent comprehensive clinical evaluations, including clinical presentations, hearing threshold, imaging studies, surgical approaches, and prognosis. A grading system was developed based on the tumor location and adjacent neurovascular structures involvement according to imaging and intraoperative findings. Results: In this study, grade II tumors were the most common (13/31), followed by grades I (7/31), III (7/31), and IV (4/31) tumors. Seven grade I patients received the subtemporal middle cranial fossa approach (SMCF) combined with the canal wall up mastoidectomy and tympanoplasty (CWUT). Nine grade II patients underwent SMCF combined with subtotal petrosectomy (SPTR), and four grade II patients underwent SMCF combined with CWUT. Seven grade III patients received SMCF combined with SPTR and dura mater reconstruction, and four grade IV patients underwent infratemporal fossa approach type B. Gross total resection was achieved in all patients, and the median follow‐up time was 30.1 months (range, 4–96 months). Three patients (one grade II, one grade III, and one grade IV) had recurrence during follow‐up, and the patient with grade III tumor had two recurrences. Conclusions: Gross total resection is the first‐line treatment for patients with D‐TGCT of the temporal bone. This novel grading system enables surgeons to select optimal surgical strategy. Long‐term follow‐up is mandatory postoperatively. Level of Evidence: 4 Laryngoscope, 132:1275–1284, 2022